Pengaruh Layanan Bimbingan Kelompok dengan Teknik Permainan Terhadap Penyesuaian Diri Siswa - Husna, Norma Nimatul; Sutoyo, Anwar (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research was conducted based on phenomena that occur in grade V SD Negeri Sumurrejo 01 Gunungpati Semarang that has characteristics of adaptability that is still low. The purpose of this research is to find empirical evidence regarding the influence of the tutoring service group with the technique of the gametowards the adaptability of students. This type of research is research experiments. The research was conducted with nine times the grant of preferential treatment on grade V SD Negeri Sumurrejo 01 Gunungpati, Semarang, with the subject of 10 students. The data collection methodused is the psychological scale. Analytical techniques descriptive analysis of the data using the percentage and wilcoxon test. The results showed an increase in adaptability in students achieving 19,96%. This indicates that there is an influence of the grant guidance group with games against conformity engineering students.